At Most Twin Outer Perfect Domination Number Of A Graph - et. al., G. Mahadevan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A Set In A Graph G Is Said To Be At Most Twin Outer Perfect Dominating Set If For Every Vertex , And Has At Least One Perfect Matching. The Minimum Cardinality Of At Most Twin Outer Perfect Dominating Set Is Called At Most Twin Outer Perfect Domination Number And Is Denoted By . In This Paper, We Initiate A Study Of This Parameter.